Pengaruh Keterampilan Kerja, Kompensasi, dan Motivasi Terhadap Kinerja Karyawan (Studi Kasus Pada karyawan Bagian Produksi PT. Sumber Wijaya Sakti) - Chaliza, Aniek Noer (Peneliti.net, 2023)
This study began with findings showing that employee performance at PT. Sumber Wijaya Sakti where employees are less than optimal in carrying out their work, so that the company's productivity in its targets is not achieved optimally. It can be seen in the monthly production results which show that employees who worked during a certain period were only able to produce a number of cigarettes that were much lower than the target that had been set as well as the finding that the variables that explain the phenomenon of employee performance are still different which then leads to the formulation of the problem regarding